Anchoring Your Big Data Environment - Regha, S; Manimekalai, M (International Journal of Computer Sciences and Engineering, 2025)
Security and protection issues are amplified by the volume, assortment, and speed of Big Data. The decent variety of information sources, arrangements, and information streams, joinExternalize data security when possible and d with the gushing idea of information procurement and high volume make one of kind security dangers. This paper points of interest the security challenges when associations begin moving touchy information to a Big Data store like Hadoop. It distinguishes the diverse danger models and the security control structure to address and alleviate security hazards because of the recognized risk conditions and use models. The system laid out in this paper is likewise intended to be circulation skeptic